Studi Kuat Tekan Beton dengan Substitusi Serbuk Kapur Tohor sebagai Pengganti Semen Portland - Asroful Anam; Arie Taveriyanto (Jurnal Kridatama Sains dan Teknologi, 2026)
Large-scale Portland cement production contributes significant CO₂ emissions and increases construction costs. This study aims to analyze the effect of quicklime powder (CaO) substitution on concrete compressive strength and to determine the substitution level that still meets the target compressive strength. A laboratory experimental method was used with three substitution variations: 0% (control), 2.5%, and 5.5%. Each variation comprised 3 cube specimens measuring 15×15×15 cm (9 specimens total), with a concrete mix designed according to SNI 7656:2012 for a planned strength of K-125. Mix design parameters: w/c = 0.56; planned slump 75–150 mm; composition per m³: cement 366.07 kg, sand 693.78 kg, gravel 1,085.15 kg, water 205 liters. Compressive strength testing was conducted at 28 days using a Compression Testing Machine (CTM) per SNI 1974:2011, with age limited to 28 days as it represents final concrete strength per SNI 1974:2011 and ASTM C39/C39M. Results showed mean compressive strengths of: 0% = 19.78 MPa (SD = 1.28 MPa; CV = 6.5%), 2.5% = 17.95 MPa (SD = 0.65 MPa; CV = 3.6%), and 5.5% = 15.72 MPa (SD = 4.44 MPa; CV = 28.2%). Strength reduction was caused by the dilution effect, low CaO reactivity compared to Portland cement, and non-uniform particle distribution at higher substitution levels. The 2.5% substitution still met the target compressive strength (16.89 MPa) and is considered feasible, while 5.5% did not. The optimal substitution level is ≤2.5%